Recovery linked to life history of sessile epifauna following exclusion of towed mobile fishing gear. Issue 3 (23rd January 2018) - Kaiser, Michel J.; Hormbrey, Samantha; Booth, Jonathan R.; Hinz, Hilmar; Hiddink, Jan G.
Abstract: The use of reserves as conservation tools is widespread. However, evaluating the effectiveness of reserve implementation for long‐lived species has been problematic as it requires sampling programmes over long timescales that are appropriate to species' longevity and recovery rates. In the sea, towed bottom fishing gears alter the biodiversity and ecosystem services provided by benthic communities and habitats. Marine reserves have been used to manage these impacts but our understanding of the drivers of their effectiveness for the conservation of temperate reefs is incomplete. We examined the effectiveness of marine reserves for recovery of temperate reef fauna in relation to their life history. We used an underwater video to sample six species with different life histories across 60 sites that varied in the duration of protection from towed mobile fishing gear at 0, 1, 8 and 10 years. Species with a high dispersal potential and less habitat specific requirements such as soft corals and king scallops recovered to close to their carrying capacity in <3 years. In contrast, the longer‐lived Ross coral and pink seafans increased in abundance but had not fully recovered; with their projected recovery time being 17–20 years. Ongoing recovery was evident for long‐lived species as their mean body size increased significantly across all treatments, whereas shorter‐lived species such as queen scallops did not change in size and were assumed to have fully recovered. Synthesis and applications . This study shows that the recovery rates of biota depend on life‐history factors, such as larval longevity and dispersal potential. Recovery for species that had low dispersal potential and specific habitat requirements was slow and could take >20 years. This suggests activities such as bottom trawling or dredging should be avoided where such species occur if their conservation is an objective. In contrast, species with high dispersal potential and less habitat specific requirements had shorter recovery timescales of c . 2‐3 years and would be more amenable to managed trawl frequencies in areas where activities such as fishing occur. Abstract : This study shows that the recovery rates of biota depend on life‐history factors, such as larval longevity and dispersal potential. Recovery for species that had low dispersal potential and specific habitat requirements was slow and could take >20 years. This suggests activities such as bottom trawling or dredging should be avoided where such species occur if their conservation is an objective. In contrast, species with high dispersal potential and less habitat specific requirements had shorter recovery timescales of c . 2‐3 years and would be more amenable to managed trawl frequencies in areas where activities such as fishing occur.